Independent Association of Circulating Level of Chemerin With Functional and Early Morphological Vascular Changes in Newly Diagnosed Type 2 Diabetic Patients. Issue 47 (November 2015) - Lu, Bin; Zhao, Ming; Jiang, Weimin; Ma, Jian; Yang, Cuihua; Shao, Jiaqing; Gu, Ping
Abstract : Abstract: There is growing evidence that chemerin, a novel adipokine elevated in obesity and metabolic syndromes, plays a crucial role in advanced atherosclerosis. This study aimed to determine the chemerin levels in diabetes and evaluate the effects of increased chemerin on early atherosclerosis. A total of 245 newly diagnosed diabetic patients and 148 age-matched, healthy, normal glucose tolerant (NGT) controls were enrolled. Anthropometric measurements and plasma parameters were examined, including body mass index (BMI), waist circumference, blood pressure, glucose, lipid profiles, inflammation markers, adipokines, and cell adhesion molecules. Vascular healthy was measured with brachial flow-mediated dilatation (FMD) and carotid intima-media thickness (IMT). Compared with NGT controls, plasma chemerin levels were higher in diabetic patients ( P < 0.01) and higher chemerin level was an independent risk factor of occurrence of diabetes even after metabolic profiles were adjusted (odds ratio [OR] = 1.352, 95% CI: 1.181–1.543, P < 0.01). In patients with type 2 diabetes, chemerin was positively associated with intercellular adhesion molecule-1 (ICAM-1), E-selectin, but not vascular adhesion molecule-1 (VCAM-1) and P-selectin. We also explored that plasma chemerin level was negatively associated with brachial FMD and positively with carotid IMT. Chemerin also retained a strong association with ICAM-1, FMD, and IMT even after adjusted for age, sex, and other risk factors (ICAM-1: r = 0.150, P = 0.024; FMD: r = −0.126, P = 0.001; IMT: r = 0.325, P < 0.001). By multiple linear regression analysis, plasma chemerin levels were related to ICAM-1 even after adjustments for conventional cardiovascular risk factors (β = 0.192, P = 0.017). Moreover, logistic regression analysis showed that high chemerin level was an independent predictive variable for impaired endothelial function (OR = 1.066, 95% CI: 1.012–1.142, P = 0.048) and enhanced carotid vessel thickness (OR = 1.068, 95% CI: 1.021–1.148, P = 0.035) in diabetic patients. In summary, chemerin levels are independently associated with endothelial activation and early atherosclerosis in newly diagnosed type 2 diabetes.